The Analysis of Cocoa Bean Price Fluctuation in North Kolaka Regency - Rukia Taslim; Ilma Sarimustaqiyma Rianse; La Ode Kasno Arif (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to determine the price fluctuations of cocoa beans and cocoa bean price trends. This research was conducted in North Kolaka Regency from July to December 2021. The variables in this study were price fluctuations and cocoa bean price trends. This study was analyzed using price change and linear trend analysis from 2019 to 2021. Based on the results of the study, the price of cocoa beans fluctuated during the last 3 years (2019-2021), where the highest percentage change in prices occurred in December 2019 at 41% and September 2021 by 39%, and the lowest price percentage change in May 2020 by 13% with an average change during the 2019 to 2021 period of 26% and the trend of cocoa bean prices in North Kolaka Regency using the linear trend formula (Y = 2339 + 134.87 x) shows a changing trend towards an increase of IDR134.87/month and the average price of cocoa beans for a period of 36 months (2019-2021) is IDR25,889/kg.